Mechanization in Ghana: Emerging demand, and the search for alternative supply models - Diao, Xinshen; Cossar, Frances; Houssou, Nazaire; Kolavalli, Shashidhara (Elsevier, 2014)
Influential studies in the 1980s and early 1990s drew on the Boserup–Ruthenberg theories of farming systems evolution to argue that African countries were not yet ready for widespread agricultural mechanization. Through applying the theories of farming systems evolution and of induced innovation in technical change, this paper shows that demand for certain mechanized farming operations particularly plowing has emerged even among smallholders, suggesting that supply issues may now be the main constraint to successful mechanization. We therefore adopt a supply chain approach to analyze two types of mechanization practices in Ghana, i.e., a recent state-led mechanization program and the private sector-led service hiring market, against an international perspective by drawing on three Asian supply models. We identify two major flaws in existing policies. First, the agricultural mechanization service centers that the government promotes fail to use tractors services with sufficient intensity. Second, direct importation of agricultural machinery by the government inhibits imports of appropriate and affordable machinery. In contrast, the development of mechanized service hiring market in which medium and large scale farmers who are tractor owners provide hiring-out services to small-scale farmers represents a promising model for sustainable mechanization in Ghana. This private sector-led second model is consistent with international experiences.